(untitled) (Journal of Partial Differential Equations, 2010)
In this paper we consider regularities of radial solutions to the degenerate complex Hessian equations. Our results generalize some results for Monge-Ampere equation in [Monn, Math. Ana. 275 (1986), pp. 501-511] and [Delanoe, J. Diff. Eqn. 58 (1985), pp. 318-344].